Inspeksi Alat Pemadam Api Ringan dalam Upaya Mengidentifikasi Potensi Bahaya - Laili Nurjannah Yulistiyana; Cucu Herawati; putri iklimah; iin kristanti; Nur Arofah; Dewi Mutiah; Didi Taswidi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
INSPECTION OF LIGHT FIRE EXTINGUISHERS IN AN EFFORT TO IDENTIFY POTENTIAL HAZARDS. Humans, environmental conditions, and management can cause fires. Fire is an uncontrolled fire, meaning it is beyond human control. APAR is a light fire extinguisher used to extinguish or control fires. Providing an APAR (very effective Light Fire Extinguisher) installation is one way to prevent and control fires. The purpose of this community service activity is to inspect light fire extinguishers in an effort to identify potential hazards. The methods used are Observation, interviews, and documentation studies. The APAR inspection activity was carried out on March 1-16, 2023, attended by SHE Department staff and the Fire Fighting Team. The priority problems obtained were to review the Job Safety Analysis (JSA) regarding the 2015 Safety Inspection and refresh the delivery of the JSA to the fire fighting team.